Glial modulation of synapse development and plasticity: oligodendrocyte precursor cells as a new player in the synaptic quintet - Akinlaja, Yetunde O.; Nishiyama, Akiko (Frontiers in Cell and Developmental Biology, 2024)
Synaptic communication is an important process in the central nervous system that allows for the rapid and spatially specified transfer of signals. Neurons receive various synaptic inputs and generate action potentials required for information transfer, and these inputs can be excitatory or inhibitory, which collectively determines the output. Non-neuronal cells (glial cells) have been identified as crucial participants in influencing neuronal activity and synaptic transmission, with astrocytes forming tripartite synapses and microglia pruning synapses. While it has been known that oligodendrocyte precursor cells (OPCs) receive neuronal inputs, whether they also influence neuronal activity and synaptic transmission has remained unknown for two decades. Recent findings indicate that OPCs, too, modulate neuronal synapses. In this review, we discuss the roles of different glial cell types at synapses, including the recently discovered involvement of OPCs in synaptic transmission and synapse refinement, and discuss overlapping roles played by multiple glial cell types.